Yesus Kristus Juru Ruwat Manusia: Sebuah Pendekatan Semiotika dalam Gereja Kristen Jawa - Kristriyanto Kristriyanto (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2018)
Ruwatan is a form of ceremony in Javanese society that aims to free man from bad luck or the calamity that would befall him. The term